« La maternité refusée » dans La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres - Lévesque, Andrée (La norme et les déviantes: des femmes au Québec pendant l'entre-deux-guerres, 1989)
Etude socio-historique des comportements sexuels de la femme au Québec sur une période de vingt ans. Les trois premiers chapitres traitent de la norme sociale qui s'impose aux femmes par rapport à la maternité et à la sexualité. Le reste concerne diverses formes de déviance sociale par rapport à trois catégories de comportements : le refus de la maternité (contraception, avortement, infanticide, abandon d'enfants); la maternité en dehors du mariage (mères célibataires); la sexualité commercialisée (prostitution).
Keywords: amérique du nord; amériques; approches et analyses; canada; corps; corps féminin; cours; discipline; famille; his4523; histoire; hétérosexualité; justice reproductive; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sofia; thématiques

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

chapitre 3, « Les couvents comme expression organisée des aspirations des femmes » dans Profession: religieuse : un choix pour les Québécoises, 1840-1920 - Danylewycz, Marta; Linteau, Paul-André; Prentice, Alison; Westfall, William (Profession: religieuse : un choix pour les Québécoises, 1840-1920, 1988)
Marta Danylewycz s'intéresse à 2 communautés: les soeurs de Notre-Dame et de la Miséricorde, qui rassemblent près du cinquième de la population religieuse féminine au tournant du siècle.
Keywords: 1800-1899; 1840-1849; 1850-1859; 1860-1869; 1870-1879; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques

Homeward bound: American families in the Cold War era - May, Elaine Tyler (Basic Books, 1988)
In the 1950s, the term "containment" referred to the foreign policy-driven containment of Communism and atomic proliferation. Yet in Homeward Bound May demonstrates that there was also a domestic version of containment where the "sphere of influence" was the home. Within its walls, potentially dangerous social forces might be tamed, securing the fulfilling life to which postwar women and men aspired. Homeward Bound tells the story of domestic containment - how it emerged, how it affected the lives of those who tried to conform to it, and how it unraveled in the wake of the Vietnam era's assault on Cold War culture, when unwed mothers, feminists, and "secular humanists" became the new "enemy." This revised and updated edition includes the latest information on race, the culture wars, and current cultural and political controversies of the post-Cold War era.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; amériques; approches et analyses; cold war; cours; discipline; division of household labor; division sexuelle du travail; famille; guerre froide; his4443; histoire; histoire des femmes*; histoire du féminisme; histoire et politique; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique; états-unis

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis

Le Bordel: Milieu De Travail Contrôlé - Lévesque, Andrée (Labour / Le Travail, 1987)
PENDANT LONGTEMPS, des milliers de femmes gagnèrent leur vie dans des bordels à Montréal. L'étude de leur milieu de travail pendant les années vingt et trente révèle une organisation hiérarchique et des conditions dont le contrôle échappait aux principales intéressées. L'appareil judiciaire et policier, les organisations de réformes sociales, le clergé et les médecins hygiénistes affectaient, par la tolérance ou la répression, le cadre dans lequel s'exerçait la prostitution. Plus directement, les souteneurs, les tenancières et leurs gérantes déterminaient les conditions quotidiennes de travail. Les changements observés pendant toute cette période sont plus imputables à la vigilance policière qu'aux fluctuations économiques ou aux efforts des travailleuses elles-mêmes.
Keywords: 1900-1999; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; montréal; premier cycle; prostitution; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; thématiques; travail; travail du sexe; travail du sexe-prostitution

Maria W. Stewart, America's first Black woman political writer : essays and speeches - Stewart, Maria W. (Indiana University Press., 1987)
En rassemblant et en présentant les œuvres de Stewart, Richardson offre aux lecteurices l'occasion d'étudier les pensées et les paroles de cette influente militante noire, précurseuse de Frederick Douglass et de Sojourner Truth et première noire américaine à donner des conférences pour la défense des droits des femmes, la plaçant dans le contexte du mouvement abolitionniste tourbillonnant.
Keywords: 1800-1899; afro-féminisme; amériques; antiesclavagisme; approches et analyses; cours; discipline; droits des femmes*; fem1000; femmes* afro-américaines; féminismes noirs; histoire; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis

« Vivre au pensionnat : le cadre de vie des couventines » dans Les couventines: l'éducation des filles au Québec dans les congrégations religieuses enseignantes, 1840-1960 - Dumont, Micheline; Fahmy-Eid, Nadia (Les couventines: l'éducation des filles au Québec dans les congrégations religieuses enseignantes, 1840-1960, 1986)
Keywords: 1800-1899; 1900-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; droit des femmes*; his4523; histoire; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; thématiques

La naissance et la petite enfance en Nouvelle Angleterre à l'époque coloniale 1630-1750 - Bergamasco-Lenarda, Lucia (Revue d’histoire moderne et contemporaine, 1984)
Keywords: 1600-1699; 1700-1799; amériques; approches et analyses; colonialisme; colonisation britannique; condition de l'enfant; cours; discipline; enfance; famille; his4443; histoire; maternité; patriarcat; petite enfance; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis

Maitresses de maison, maitresses d'ecole: femmes, famille et education dans l'histoire du Quebec - Fahmy-eid, Nadia; Barry, Francine (Studies on the history of Quebec, 1983)
Recueil de quatorze études, par douze spécialistes, sur des aspects des rapports entre les femmes et l'éducation, et les femmes et la famille à diverses époques de l'histoire du Québec. Un bilan des recherches sur les questions précède ces études.
Keywords: 1600-1699; 1700-1799; 1800-1899; amérique du nord; amériques; approches et analyses; canada; cours; discipline; famille; his4523; histoire; histoire des femmes*; histoire et politique; patriarcat; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; éducation

La lutte pour le droit à l’avortement (1969-1981) - Lamoureux, Diane (Revue d'histoire de l'Amérique française, 1983)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amérique du nord; amériques; avortement; canada; discipline; front de libération des femmes; histoire; justice reproductive; militance; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques